1988
DOI: 10.1104/pp.88.4.961
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Elemental Sulfur in Isolated Intact Spinach Chloroplasts

Abstract: ABSTRACrIncubation of intact spinach (Spinacia oleracea L.) chloroplasts in the presence of 35SO42-resulted in the light-dependent formation of a chloroform-soluble sulfur-containing compound distinct from sulfolipid. We have identified this compound as the most stable form (S%) of elemental sulfur (S°, valence state for S = 0) by mass spectrometry. It is possible that elemental sulfur (S°) was formed by oxidation of bound sulfide, i.e. after the photoreduction of sulfate to sulfide by intact chloroplasts, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Production of elemental S in eukaryotes is by an uncharacterized pathway, which may involve oxidation of sulfide. It has been postulated that a sulfide oxidase may be responsible for elemental S production in spinach chloroplasts (Joyard et al, 1988) and oxidation by cytochromes has been suggested in the green alga Chlorella fusca (Kraus et al, 1984). Both of these enzymes have been implicated in bacterial production of S 0 (Moriarty and Nicholas, 1970;Gray and Knaff, 1982;Cusanovich et al, 1991;Sasahira et al, 1992;Bang et al, 1995;Pattaragulwanit et al, 1998).…”
mentioning
confidence: 99%
“…Production of elemental S in eukaryotes is by an uncharacterized pathway, which may involve oxidation of sulfide. It has been postulated that a sulfide oxidase may be responsible for elemental S production in spinach chloroplasts (Joyard et al, 1988) and oxidation by cytochromes has been suggested in the green alga Chlorella fusca (Kraus et al, 1984). Both of these enzymes have been implicated in bacterial production of S 0 (Moriarty and Nicholas, 1970;Gray and Knaff, 1982;Cusanovich et al, 1991;Sasahira et al, 1992;Bang et al, 1995;Pattaragulwanit et al, 1998).…”
mentioning
confidence: 99%
“…2b). Sulphate is the principal source for elemental S in plants: the sulphate is reduced to sulphide in several steps, mainly in chloroplasts (Joyard et al ., 1988), and the sulphide is then incorporated into cysteine, whose formation is practically the only point of entry of reduced sulphur into organic compounds in plants. The cysteine is partially converted to methionine or glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…So far the mechanism of S 0 formation solely present in resistant plant tissue remains uncharacterized, and only few possible metabolic pathways of S 0 synthesis in higher plants have been discussed. A non‐enzymatic but also an enzymatic oxidation might contribute to generation of S 0 (Joyard et al , Cooper and Williams ). An association with the reductive S assimilation in form of the degradation of cysteine (Cys) has been proposed to contribute to S 0 formation (Cooper and Williams ).…”
Section: Introductionmentioning
confidence: 99%